Decidual NR2F2-Expressing CD4+ T Cells Promote TH2 Transcriptional Program During Early Pregnancy - Lin, Yikong; Zhang, Di; Li, Yangyang; Li, Yunyun; Li, Bin; Du, Meirong (Frontiers in Immunology, 2021)
A unique immunotolerant microenvironment with Th2 bias in the decidua provides an essential security for successful pregnancy. The disorganized maternal-fetal immune tolerance contributes to more than 50% of unexplained recurrent spontaneous abortion (RSA). How the Th2 bias is developed at the maternal-fetal interface remains undefined. NR2F2, a member of steroid/thyroid nuclear receptor superfamily, is endowed with diverse importance in cell-fate specification, organogenesis, angiogenesis, and metabolism. Here, we showed that NR2F2 was absolutely highly expressed in decidual CD4+T(dCD4+T) cells, but not in peripheral circulating CD4+T cells during early pregnancy. Decidual NR2F2-expressing CD4+T cells dominantly produced Th2 cytokines. In unexplained RSA patients, NR2F2 expression in dCD4+T cells was significantly decreased, accompanied with disordered phenotype of dCD4+T cells. Furthermore, overexpression of NR2F2 promoted the Th2 differentiation of naive CD4+T cells. Immunoprecipitation experiment confirmed the binding relationship between GATA-3 and NR2F2, which implied GATA-3 may be an important interactive element involved in the immunoregulatory process of NR2F2. This study is the first to reveal a previously unappreciated role for NR2F2-mediated dCD4+T cells in maternal-fetal immune tolerance and maintenance of normal pregnancy, in the hope of providing a potential biomarker for prediction and prevention of clinical unexplained RSA.